J. M. Falkner, The Code of Ordinances of the City Council of Montgomery 225, § 518 (1879) - (:unkn) unknown (My University, 1879)
Prohibited carrying of a concealed Bowie knife, pistol, air gun, slungshot, brass knuckles, or other deadly or dangerous weapon. Punishable by a fine of $1-100.
Keywords: CARRY - CONCEALED